2005
DOI: 10.1093/humrep/deh825
|View full text |Cite
|
Sign up to set email alerts
|

Administration of B-group vitamins reduces circulating homocysteine in polycystic ovarian syndrome patients treated with metformin: a randomized trial

Abstract: These findings suggest that B-group vitamins and folic acid administration counteract the Hcy-increasing effect seen with metformin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
63
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 61 publications
0
63
1
2
Order By: Relevance
“…Our study found no differences in the absolute level of serum vitamin B 12 and folate between women with PCOS and matched controls, but we found negative correlations between serum folate and fasting insulin, HbA 1c , and vitamin C levels (Table II). Our findings suggest that the role of vitamin B 12 and folate in the pathogenesis of PCOS is not yet clear.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Our study found no differences in the absolute level of serum vitamin B 12 and folate between women with PCOS and matched controls, but we found negative correlations between serum folate and fasting insulin, HbA 1c , and vitamin C levels (Table II). Our findings suggest that the role of vitamin B 12 and folate in the pathogenesis of PCOS is not yet clear.…”
Section: Discussioncontrasting
confidence: 52%
“…In conclusion, the serum levels of vitamins A, B 12 , C, and D and Zn may change in patients with PCOS. The findings in this study should be investigated with further trials in order to obtain new insights into PCOS.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations